Is there a European Business Cycle? - Michael Artis (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper uses quarterly GDP data for some 30 years up to and including 2001, to examine the identity and development of the European business cycle. Cycles are identified by using a band-pass filter version of the Hodrick-Prescott filter and affiliations are examined using clustering techniques and classical multidimensional scaling applied to cross-correlations and other measures of cyclical sympathy. Twenty-three (23) countries are examined, of which 15 are European. The sample is divided into three 10-year periods to examine changes in affiliation. The overall verdict is that it is quite hard to discern a homogenous or developing European cycle with these data. Put loosely, globalization may be proceeding as fast as Europeanization.
Keywords: 330